Pengaruh Tingkat Kekayaan Daerah, Ketergantungan Daerah dan Upaya Pajak terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus pada Pemerintah Kabupaten/Kota di Provinsi Jawa Barat Tahun 2019-2023) - Rahayu, Yunita Sri; Hendaris, Raden Budi (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of regional wealth level, regional dependence, and tax efforts on the financial performance of local governments in 27 regencies and cities in West Java Province during the 2019–2023 period. The data used are sourced from secondary data in the form of APBD Budget Realization Reports and GRDP. The study population covers all district/city governments in West Java Province during that period. The analysis technique used is multiple linear regression. The results of this study reveal that simultaneously there is a significant influence between the variables of regional wealth level, regional dependence, and tax efforts on the financial performance of local governments in regencies and cities in West Java Province in 2019–2023. However, partially the 3 independent variables in this study show different variations, namely the regional wealth level variable has a positive effect on the financial performance of local governments, the regional dependence variable has a negative effect, and the tax efforts variable does not have a significant effect on the financial performance of local governments in regencies and cities in West Java Province in 2019–2023.